2012
DOI: 10.1007/s00405-012-2173-6
|View full text |Cite
|
Sign up to set email alerts
|

Concha bullosa surgery and the distribution of human olfactory neuroepithelium

Abstract: In bullous middle turbinate surgery, controversy exists over which side of the bullous middle turbinate should be removed, as the distribution of human olfactory neuroepithelium is unclear. This study evaluated whether the middle turbinate tissue of patients undergoing endoscopic concha bullosa surgery contains functional olfactory epithelium. This prospective clinical study was conducted in tertiary referable center. It detected 70 conchae bullosa in 48 patients with sinonasal symptoms, who underwent paranasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Smell function is essential for enjoying life, personal mood behavior, and even cautionary alerts . There are still questions to be answered concerning in which parts of the middle turbinate olfactory neurofibers exist …”
Section: Introductionmentioning
confidence: 99%
“…Smell function is essential for enjoying life, personal mood behavior, and even cautionary alerts . There are still questions to be answered concerning in which parts of the middle turbinate olfactory neurofibers exist …”
Section: Introductionmentioning
confidence: 99%
“…It is known that middle turbinate has a role in the olfactory function and the precise anatomical distribution of olfactory neuroepithelium is unknown. Although, there are many studies on the olfactory epithelium of nasal cavity, only Apuhan et al 4 studied olfactory epithelium of concha bullosa and found more nerve tissues on a lateral surface of concha. Recent studies show that olfactory mucosa is distributed more anteriorly and inferiorly than previously described dorsoposterior and also is presented in the surface epithelium of the lower medial surface of the middle turbinates.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to know for endonasal surgery that the olfactory neuroepithelial is situated within the olfactory cleft of the nasal cavity and extends to the upper portion of the nasal septum and onto the superior and middle turbinates to varying degrees [2]. Apuhan et al [1] had found olfactory nerve tissue at least in the medial part of the middle concha bullosa than the other parts of concha in their research and they suggest to open medial part of the concha bullosa in concha bullosa surgery. We agree with their opinion.…”
mentioning
confidence: 99%
“…To the Editor, We read the article titled ''Concha bullosa surgery and the distribution of human olfactory neuroepithelium'' which was written by Apuhan et al [1] in your journal. It is a good clinical research.…”
mentioning
confidence: 99%